Robot Three Dimensional Space Path-planning Applying the Improved Ant Colony Optimization - Ming Zhao; Dai Yong (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
To make robot avoid obstacles in 3D space, the Pheromone of Ant Colony Optimization（ACO）in Fuzzy Control Updating is put forward，the Pheromone Updating value varies with The number of iterations and the path-planning length by each ant . the improved Transition Probability Function is also proposed，which makes more sense for each ant choosing next feasible point .This paper firstly, describes the Robot Workspace Modeling and its path-planning basic method, which is followed by introducing the improved designing of the Transition Probability Function and the method of Pheromone Fuzzy Control Updating of ACO in detail. At the same time， the comparison of optimization between the pre-improved ACO and the improved ACO is made . The simulation result verifies that the improved ACO is feasible and available. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7723